(untitled) (Journal of Dentistry and Allied Science, 2025)
Introduction: Toothbrushes can become contaminated with oral and environmental pathogens, posing infection risks. This study evaluates how glycemic control and toothbrush storage location jointly affect microbial contamination in diabetic patients. Methods: In this cross-sectional study (Rajshahi Medical College), 60 participants (30 diabetics, 30 non-diabetic controls) provided used toothbrushes (≥2 months old) and clinical data via questionnaire. Diabetic subjects were categorized by HbA1c: good (<7%), moderate (7–9%), or poor (>9%) glycemic control (10 per category). Each subject reported toothbrush storage (washroom [WR] vs. non-washroom [NWR]). Toothbrush heads were aseptically processed in sterile saline; aliquots were cultured on selective media (Blood Agar, MacConkey Agar, Sabouraud Dextrose Agar) to isolate bacteria and yeasts (e.g., Streptococcus mutans, Staphylococcus aureus, Escherichia coli, Pseudomonas spp., Candida). Statistical analysis (SPSS) used chi-square tests and Pearson correlation to assess associations, with p≤0.05 considered significant. Results: All toothbrushes (100%) were culture-positive, with S. mutans the most prevalent isolate. Contamination rates and species diversity were significantly higher in diabetics, especially with poor glycemic control . Poor-control diabetics showed elevated prevalence of S. aureus ( 80%, p<0.01), Candida spp. ( 76.7%, p<0.01), and E. coli ( 83.3%, p<0.05) on their brushes. Separately, washroom-stored brushes (all subjects) had significantly more enteric bacteria: E. coli contamination was 86.6% (WR) vs. 46.6% (NWR), and Pseudomonas 80.0% vs. 53.3% (p<0.05). This confirms that bathroom aerosols and moisture enhance toothbrush contamination. The highest contamination occurred in brushes from poorly controlled diabetics stored in washrooms. Notably, poor HbA1c correlated strongly with greater microbial diversity (r=0.72, p<0.001). Conclusion: Both poor glycemic control and unhygienic storage significantly increase toothbrush microbial burden. Diabetic patients, especially with high HbA1c, may harbor more oral pathogens on their brushes, and washroom storage further elevates enteric contamination. These findings underscore the need for patient education on glycemic management and proper toothbrush hygiene (e.g., storing brushes away from toilets and changing them regularly) to reduce infection risk. Journal of Dentistry and Allied Science, Vol. 8 No 1: 22-27